PARENTAL ENGAGEMENT IN ACCOMPANYING KIDS LEARNING ENGLISH THROUGH MONKEY STORIES APPLICATION DURING COVID-19 LOCKDOWN - Ni Komang Purwaningsih; Si Putu Agung Ayu Pertiwi Dewi; Ni Putu Lindawati (Yavana Bhasha : Journal of English Language Education, 2022)
Coronavirus disease 19 which has changed every aspect in the world, especially in education aspect brought a significant impact. One of them is changing the learning system at schools. Teaching and learning process turn to use online platforms as a form of learning method online way. Therefore parents and teachers are passionately looking for best ways to facilitate online learning, one of them is by aplying monkey stories to introduce English for the kids. This study aimed at determining the parental engagement in accompanying kids learning English through monkey stories application during covid-19 lockdown. This study was a qualitative research by using observation, interview, and documentation as data collection techniques. This study found four themes including: 1) activities followed by the kids using monkey stories application, 2) description of parenting patterns applied at home, 3) the role of parents in assisting the use of monkey stories application, and 4) the effect of monkey stories application on kids’ ability in comprehending English. This study is expected had a fruitful meaning for parents in assist their kids during study at home therefore the kids still feel the school circumstances at home and parents can be active and creative learning partners for their kids at home